Bibliographic guide to dance. - New York Public Library. Dance Collection (Boston G. K. Hall., 1997)
Annual
Data also contained in: Index to dance periodicals.
Guides for 1975- published in 2 or more vols.
Issued as a supplement to: New York Public Library. Dance Collection. Dictionary catalog of the Dance Collection.
Keywords: New York Public Library. -- Dance Collection; Dance -- Bibliography -- Catalogs